The Potential Barriers and Benefits of an Online Physical Activity Program during the COVID-19 Restrictions: Latrobe Virtual Streetgames. A Qualitative Study. Issue 1 (2nd January 2023) - Kemel, Paul N.; Porter, Joanne E.; Coombs, Nicole
ABSTRACT: Background: COVID-19 saw the global reduction of many physical activity programs. To maintain engagement, many programs adjusted their delivery to online formats. Purpose: To explore the impact that a youth targeted virtual community exercise program had on its participants during the COVID-19 pandemic. Methods: Seven participants of Virtual Streetgames took part in a semi-structured one-on-one interview, with questions around the impact of COVID-19, in addition to their view on the virtual program. Results: Three major themes were identified. "Dawning of a new world" described the changes that occurred due to the pandemic. "Traveling together" identified the difficultly to maintain regular wellbeing activities. "Making a difference" contextualized how the virtual delivery was able to influence participants. Discussion: The COVID-19 pandemic had a significant impact on the participants physical, mental and social health. The use of an online physical activity program had some positive impacts on health, however it did not seem to warrant the same level of engagement when compared to face-to-face. Translation to Health Education Practice: The study helped identify those who are at risk of both short and long-term health impacts due to the COVID-19 pandemic. Additionally, it provided information on how virtual innovative interventions can influence wellbeing outcomes. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars